2017
DOI: 10.1038/s41598-017-04120-x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of human Rogdi provides insight into the causes of Kohlschutter-Tönz Syndrome

Abstract: Kohlschutter-Tönz syndrome (KTS) is a rare autosomal-recessive disorder of childhood onset characterized by global developmental delay, spasticity, epilepsy, and amelogenesis imperfecta. Rogdi, an essential protein, is highly conserved across metazoans, and mutations in Rogdi are linked to KTS. However, how certain mutations in Rogdi abolish its physiological functions and cause KTS is not known. In this study, we determined the crystal structure of human Rogdi protein at atomic resolution. Rogdi forms a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
(47 reference statements)
2
10
0
Order By: Relevance
“…19 Although the function of the ROGDI gene is not fully clarified, it has been suggested that it is responsible for efficient signals for presynaptic targeting. [19][20][21] Riemann et al 19 also concluded that Rogdi could affect neuronal migration, axonal pathfinding, or synapse formation in a subset of neurons early during development, causing a neurodevelopmental phenotype. Although it has been reported that Rogdi is expressed in the stage of odontogenesis in mouse embryos, 22 the precise role in dental phenotypes of Kohlschütter-Tönz syndrome has not yet been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…19 Although the function of the ROGDI gene is not fully clarified, it has been suggested that it is responsible for efficient signals for presynaptic targeting. [19][20][21] Riemann et al 19 also concluded that Rogdi could affect neuronal migration, axonal pathfinding, or synapse formation in a subset of neurons early during development, causing a neurodevelopmental phenotype. Although it has been reported that Rogdi is expressed in the stage of odontogenesis in mouse embryos, 22 the precise role in dental phenotypes of Kohlschütter-Tönz syndrome has not yet been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure reveals that ROGDI protein contains two distinct domains α and β. The α domain consists of four helices that form a left-handed four-helix bundle, and the β domain comprises two β-sheets each containing four antiparallel β-strands and flanked by two short α-helices (Lee et al, 2017). Typical leucine zipper proteins, such as transcription factors, dimerize to bind to DNA.…”
Section: Genetic and Molecular Aspectsmentioning
confidence: 99%
“…3 ) although the exclusive nuclear localization might not be a prerequisite for transcriptional activities. We recently reported the crystal structure of human ROGDI protein 62 and showed that, unlike other bZIP transcription factors, human ROGDI protein exists as a monomer containing two structurally distinguishable domains (designated as α and β domains, respectively) (Supplementary Fig. 2a ).…”
Section: Discussionmentioning
confidence: 99%